MENINGKATKAN KETERAMPILAN MENULIS DENGAN MEDIA PAPAN SUSUN KALIMAT PADA SISWA KELAS DUA SD SEMANGAT DALAM LIMA - Mirna Mirna; Patra Aghtiar Rakhman; Nana Hendra Cipta; Jumadi; Dwi Wahyu Candra Dewi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Abstrak The aim of carrying out this research is to improve students' skills in arranging words into sentences using sentence building board media. The subjects of this research were class II students at SDN Selamat Dalam Lima. This research has several stages for carrying out research, namely (1) planning, (2) implementation, (3) observation, (4) reflection. Data will be collected in this research using observation and test techniques in the form of learning implementation sheets, several scrambled words regarding skills in arranging words into sentences. Learning in the 21st centu223ry is creative and innovative learning with the use of sentence board learning media which is suitable as an innovative learning media. Based on the results of the preliminary study, it shows that this sentence construction learning media is effective and not monotonous and based on the literature study, this sentence arrangement board has many advantages.